Latin America and the Caribbean : projections 2006-2007 (CEPAL SantiagoCL, 2006)
Reviews the current perceptions of international economic analysts regarding the global economic scenario. Attempts to identify the risk factors of greatest impact on some countries in the region. Highlights the most characteristic features of growth in the countries of the region. Revises the results of the country projections, identifying the most important factors of growth in 2006-2007.
Bibliography: p. 51